ANALISIS TRANSPORTASI KAWASAN NIAGA PANGLIMA BATUR KOTA SAMARINDA - Tukimun Tukimun; Rosa Agustaniah (Rang Teknik Journal, 2023)
The Panglima Batur Commercial Area is a shopping area which is the center of commercial activity in Samarinda City. Around Jalan Panglima Batur there are several shopping centers such as Pasar Pagi, Mesra Indah Mall, shops along Jalan Panglima Batur and the Citra Niaga Commercial Area which is a "Landmark" of Samarinda City. The obstacle faced in the area is congestion on roads, especially Jalan Panglima Batur from morning to evening. The influence of on street parking is a problem in the area. Based on the results of an analysis of the congestion conditions on the Panglima Batur road, Samarinda City, to the traffic load in the trading area around Citra Niaga and Pasar Pagi with on street parking, there was a decrease in road capacity of 53.02%, a decrease in speed of 37.96 % and a decrease in road service level (LOS) from LOS C (Q/C = 0.49) to LOS E (Q/C = 0.92). The solution to the problem is eliminating on-street parking and managing parking with the concept of parking pockets such as creating multilevel parking in the Mesra Indah Mall parking area with the concept of Public Private Partnership (KPS).